DATA ANALYSIS OF THE RESULTS SUBMITTED IN THE PROFICIENCY TEST OF IAEA-CU-2006-06 (ANCIENT CHINESE CERAMIC) – MORE DATA INPUT USING K0-INAA - Wasim, M.; Arif, M.; Zaidi, J. H.; Daud, M. (The Nucleus, 2010)
In the first part of this paper, the data submitted in the proficiency test (PT) conducted under the IAEA co-ordinated research project has been statistically evaluated. The data contains elemental concentrations determined in the IAEACU-2006-06 (ancient Chinese ceramic) powder by different laboratories using various analytical techniques. The analysis has been performed by using relative deviation and relative standard deviation. The use of rescaled sum of zscore, sum of square of z-score and principal component analysis has been suggested to determine the overall laboratory performance. The second part of the paper provides elemental concentrations of four elements (Eu, Lu, Sr and Zr) determined by our laboratory by k0-INAA. Finally, principal component analysis has been applied to get interlaboratories patterns on the scores plot. The overall analysis reveals that INAA produces results with high accuracy and precision and with good sensitivity for a large number of elements.